The Concept of Independent Learning of Early Childhood in Perenalism Perspective - Widhiyanti, Sri (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The general purpose of education is an effort to build individual character through a certain systematic and planned process. The formation of good character must start from an early age (golden age). Positive, creative, effective, fun and non-coercive early childhood learning atmosphere must be used in the character development process. This allows individuals to develop according to their desired talents and interests without any coercion as contained in the concept of independent learning. Perennialism in education is a cultural heritage from the previous generation to the new generation, in the form of eternal values ​​that are not limited by space and time, which has the aim of forming the character of students who can adapt to the times and do not leave values ​​and culture as personality traits. nation. The research used is library research in exploring related concepts. The research approach used is descriptive qualitative. Education in the perspective of perennialism places more emphasis on noble values ​​and religious norms. The philosophy of perennialism in the freedom of early childhood learning is an effort to build the character of Pancasila students who have morals, uphold the values ​​of goodness that have noble values.